Wpływ wyznawanych idei i identyfikacji politycznych na decyzje wyborcze w wyborach samorządowych - Widera, Zbigniew (Political Preferences, 2012)
Knowledge of the behavior of the electorate has both its social context, as well as eco- nomic. It identifies the social interaction on the behavior of politicians and the effects of their management, moreover reveals the motivations and determines of political sensitivity, the de- gree of social disapproval and indifference. Rationalize the cost of election campaigns, influ- ences the electoral strategies and the consequent publicity and promotion mechanisms. It also affects the way services are involved in the electoral processes of individuals and businesses. It has a number of theoretical ways of using its wide but especially a practical context. The municipal elections which are the subject of growing interest are identified in the broader electoral context, the connection with other acts of election: elections to the parliament, the European Union and in the end of the presidential elections. The media of social life more and more influence on the behavior of voters, receiving daily spectacle of self-presentation, per-manent verbalization of ideas and references to public opinion polls. Voter is willed or not to participate. This causes the increasing consistency of its behavior in the different types of elections.